Analysis of clinical characteristics and outcome of patients with previously untreated diffuse large B-cell lymphoma and renal involvement in the rituximab era - Giesen, Nicola; Krämer, Isabelle; Schwarzbich, Mark-Alexander; Ho, Anthony Dick; Witzens-Harig, Mathias (Leukemia and lymphoma, 2016)
Renal involvement in patients with lymphoma is rare but associated with poor prognosis. We analyzed characteristics and outcome of 22 patients with newly diagnosed diffuse large B-cell lymphoma (DLBCL) and renal involvement treated with a rituximab-containing regimen in curative intent. The majority of patients presented in advanced disease, 86% were Ann Arbor stage ≥ III and had an IPI score ≥ 3. Renal impairment was present in 32%. Outcome was poor with three-year progression-free survival (PFS) 44% and three-year overall survival (OS) 52% and significantly worse compared to DLBCL without renal involvement (p < 0.01). Patients with high-risk IPI had a significantly inferior prognosis compared to intermediate-risk IPI (three-year OS 0% vs. 75%, p = 0.01) as did those with renal impairment. A high rate of central nervous system (CNS) relapse (8/22) was observed. Intravenous high-dose methotrexate and intrathecal therapy showed a trend toward prolonged time to CNS relapse. Implementation of CNS prophylaxis might therefore be considered in these high-risk patients.
Gesehen am 18.06.2020